Penerapan Metode Information Search dalam Meningkatkan Prestasi Belajar Siswa Kelas IX pada Mata Pelajaran Pendidikan Agama Islam - A. Rahman (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
To support the success of the function of national education must be supported by several things, and one of the most important things is the teacher. Teachers have a very important role in the development and progress of their students. From here the teacher is required to be able to carry out the task as well as possible. In this study, the research design used was Classroom Action Research, with a participatory independent type. It has been more than ten years since classroom action research was known and widely discussed in the world of education. The term in English is Classroom Action Research (CAR). expanding vocabulary and not just fixating on material resources which are reference materials for finding answers, students are not only fixated on the explanations given by the teacher but they have to try on their own to be able to find the right answers to the questions that have been given by the teacher. The implementation of the application of the information search method in improving the learning achievement of class IX students in the Islamic Religious Education subject at SMP Negeri 2 Utan, Utan District, was carried out in 8 meetings with 2 meetings filled with UTS and Daily Deuteronomy, so in 3 cycles carried out 6 meetings per 2x delivery of material in 1 cycle.